Ultraconformable Integrated Wireless Charging Micro-Supercapacitor Skin - Chang Gao; Qing You; Jiancheng Huang; Jingye Sun; Xuan Yao; Mingqiang Zhu; Yang Zhao; Tao Deng (Nano-Micro Letters, 2024)
Highlights An ultraconformable skin-like integrated wireless charging micro-supercapacitor (IWC-MSC) could be wireless charged to store electricity into high capacitive micro-supercapacitors (11.39 F cm−3), and fits well with human surface. Building blocks of IWC-MSC skin are all evaporated by liquid precursor, and each part of the device attached firmly benefitting from the liquid permeation, forming a compact and all-in-one configuration. The electrode thickness easily regulated varying from 11.7 to 112.5 μm by controlling the volume of electrode solution precursor.